Idol dreams. 5 - Tanemura, Arina (VIZ Media, LLC, 2018)
"To pursue missed chances at love and success, 31-year-old Chikage Deguchi takes an experimental drug that changes her appearance back to how she looked at age 15. Chikage meets Tokita's girlfriend for the first time and is shocked to discover that she knows her! Even worse, she knows his girlfriend has been cheating on him..."--Page [4] of cover.